ANALISIS KURIKULUM PENDIDIKAN AGAMA ISLAM PRA DAN PASCA UNDANG-UNDANG RI NOMOR 20 TAHUN 2003 TENTANG SISTEM PENDIDIKAN NASIONAL - Asfiati Asfiati (Studi Multidisipliner: Jurnal Kajian Keislaman, 2017)
The curriculum is very strategically used as guidelines for the implementation of learning activities, which included a guide to the interaction between teachers and learners. Development and curriculum development in Islam refers to the changes in the field and the subject matter as well as the change of time, the essence of the curriculum in the educational aspects of the macro objectives. Islamic religious education curriculum Post Undang-Undang RI Nomor 20 Year 2013 on National Education System played a role important in recognizing the importance of moral education and cultural values culture based on moral values and rules that divine principle that is Almighty.